If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + 4) = 0 Reorder the terms: (-3 + x)(x + 4) = 0 Reorder the terms: (-3 + x)(4 + x) = 0 Multiply (-3 + x) * (4 + x) (-3(4 + x) + x(4 + x)) = 0 ((4 * -3 + x * -3) + x(4 + x)) = 0 ((-12 + -3x) + x(4 + x)) = 0 (-12 + -3x + (4 * x + x * x)) = 0 (-12 + -3x + (4x + x2)) = 0 Combine like terms: -3x + 4x = 1x (-12 + 1x + x2) = 0 Solving -12 + 1x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -1x)(3 + -1x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-4, 3}
| 6+11=-17-8x | | a-9/10=-3/20 | | n+6=23/4 | | m+9=49/5 | | w+8=25/3 | | 4/5+b=29/5 | | -4/7=b-4/7 | | n-5/7=-29/70 | | a-6=-25/4 | | w-10=-12 | | -5/3=t-8/9 | | d+1=4 | | x/3=12/2 | | x/3=12/3 | | 2/3+b=7/33 | | t-7/9=-1/36 | | a+9/10=-61/10 | | t/3=7 | | 35/4=k+3/4 | | a+6/7=90/7 | | w/2=7 | | t+1/8=-7/40 | | 1/10=x+2/5 | | 41/72=n+4/9 | | 10+w=14 | | 1+m=4/11 | | a-5=-45/11 | | 3d=-3 | | 4/3=x-2/3 | | b+1/3=-7/12 | | k+2/7=-61/7 | | m+2/9=83/9 |